2022
DOI: 10.1021/acs.jpca.2c02735
|View full text |Cite
|
Sign up to set email alerts
|

Reactive and Nonreactive Collisions between NO(X2Π) and O(3P) under Hyperthermal Conditions

Abstract: Quasiclassical trajectory calculations are performed for hyperthermal collisions between NO­(X2Π) and O­(3P) on recently developed potential energy surfaces for the lowest doublet and quartet states of the NO2 system. Three product channels are investigated, and their branching fractions are in reasonably good agreement with the recent crossed molecular beam study at 84 kcal/mol of collision energy. The dominant inelastic channel has a strong forward scattering bias and a high translational energy distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Although these extensive previous studies provided a detailed characterization of the N + O 2 system, both existing theoretical and experimental investigations lack information about nonreactive and reactive collisions of N + O 2 under the extreme conditions in hypersonic shock layers, where collision energies may be tens of kcal mol –1 . Caracciolo et al have recently reported an experimental study on the reverse of Reaction at a collision energy of ⟨ E coll ⟩ = 84.0 kcal mol –1 , and subsequent theoretical calculations by Lu et al have reasonably reproduced most of the measurements . In addition, theoretical studies of the NO + O reaction have been reported by Castro-Palacio et al , In the present paper, a joint experimental and theoretical investigation involving all three of these groups on the dynamics of hyperthermal N + O 2 collisions is reported.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Although these extensive previous studies provided a detailed characterization of the N + O 2 system, both existing theoretical and experimental investigations lack information about nonreactive and reactive collisions of N + O 2 under the extreme conditions in hypersonic shock layers, where collision energies may be tens of kcal mol –1 . Caracciolo et al have recently reported an experimental study on the reverse of Reaction at a collision energy of ⟨ E coll ⟩ = 84.0 kcal mol –1 , and subsequent theoretical calculations by Lu et al have reasonably reproduced most of the measurements . In addition, theoretical studies of the NO + O reaction have been reported by Castro-Palacio et al , In the present paper, a joint experimental and theoretical investigation involving all three of these groups on the dynamics of hyperthermal N + O 2 collisions is reported.…”
Section: Introductionsupporting
confidence: 61%
“…Caracciolo et al have recently reported an experimental study on the reverse of Reaction 1 at a collision energy of ⟨E coll ⟩ = 84.0 kcal mol −1 , 38 and subsequent theoretical calculations by Lu et al have reasonably reproduced most of the measurements. 39 In addition, theoretical studies of the NO + O reaction have been reported by Castro-Palacio et al 24,32 In the present paper, a joint experimental and theoretical investigation involving all three of these groups on the dynamics of hyperthermal N + O 2 collisions is reported. We focus our attention on products generated from nonreactive (1a) and reactive (1b) collisions:…”
Section: Introductionmentioning
confidence: 62%
“…Such exchange channels are known to be efficient in hyperthermal collisions. [49][50][51][52] In our calculations reported here, (R2) is either implicitly included in the WP calculations, through the use of a damping term, or explicitly included in the CSDM calculations. As shown in this work, the adiabatic exchange channel (R2b) has much larger rate coefficients than the nonadiabatic channels (R-1 and (R2a)).…”
Section: Introductionmentioning
confidence: 99%
“…In light of the present results, these reactions involving atomic nitrogen should be reviewed in future astrochemical modeling studies to determine whether their rate coefficients need to be reevaluated, supported and accompanied by simulations such as those carried out here and for other, related systems. 9,49,[61][62][63][64] In summary, this joint experimental and theoretical investigation of the N + NO reaction allowed us to determine rate coefficients for this process at room temperature and below (30-300 K). Experiments were conducted down to 50 K on a supersonic flow (Laval nozzle) type apparatus employing pulsed laser photolysis for the (indirect) production of ground state atomic nitrogen and pulsed laser induced fluorescence at VUV wavelengths to detect these atoms.…”
Section: Discussionmentioning
confidence: 96%
“…In light of the present results, these reactions involving atomic nitrogen should be reviewed in future astrochemical modeling studies to determine whether their rate coefficients need to be reevaluated, supported and accompanied by simulations such as those carried out here and for other, related systems. 9,49,61–64…”
Section: Discussionmentioning
confidence: 99%